Drama Theory as Assistant of Comparative Literature: Aspects of Expressionism in Ernst Toller's "Hinkemann" and Carlos Muñiz's "El tintero" - Pérez Jiménez, Manuel (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
This essay aims to contribute to comparative literature, working from the field of drama theory. Its hypothesis is that El tintero, by the Spanish playwright Carlos Muñiz and performed for the first time in 1961, adheres to the theoretical and creative principles formulated by the Expressionism of the early decades of 20th Century German drama. An application of Expressionist dramatic theories is carried out in the comparative analysis of Muñiz’s play and Ernst Toller’s work Hinkemann (written by the German playwright in 1921-22). The paper focuses on the composition of the plays (constituted in Expresionist drama by the genre of tragedy) and it includes a description of the entity of the agonists and the dimensions of the tragic process. The conclusion suggests that both plays are Expressionist supradramas, as both are representations of conflicts between essential humanity and supra-real dehumanization.